PENGEMBANGAN PENGEMBANGAN MEDIA FLASHCARDS DALAM PEMBELAJARAN MENULIS SISWA KELAS VI SDN 271 GRESIK: PENGEMBANGAN MEDIA PEMBELAJARAN PENDIDIKAN DASAR - Muhammad Elfat Ibrahim; Rika Rofi'atul Hajjah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop flashcard media to improve the writing skills of sixth-grade students at SDN 271 Gresik through the 4D development model (Define, Design, Develop, and Disseminate). In the Define stage, it was found that students experienced difficulties in generating ideas, selecting vocabulary, and composing descriptive paragraphs due to teacher-centered instruction and the lack of visual stimuli during writing lessons. The Design stage produced 40 colored flashcards equipped with keywords, along with learning devices aligned with the curriculum competencies. Validation by material and media experts indicated very high feasibility, scoring 91.6% and 93.3% respectively. A small-group trial showed that 90% of students understood the instructions well and were able to compose paragraphs more quickly using the flashcards. Field testing in the experimental class demonstrated a significant improvement in writing performance, with students’ average score increasing from 56.80 on the pretest to 87.25 on the posttest, achieving an N-Gain value of 0.70 (high category), while the control class only reached 0.31. Additionally, 94% of students gave positive responses, stating that the media was engaging, easy to use, and helped stimulate writing ideas. Teachers also viewed flashcards as practical and flexible for various types of texts. These findings indicate that flashcard media is effective in enhancing students’ writing skills and can serve as an alternative instructional tool for teaching writing in elementary schools.